Sim! Sou criança eu! . Dinâmicas de socialização e universos infantis em uma comunidade moçambicana - Pastore, Marina Di Napoli (2015)
Since the last decades, the studies around childhood conceptions and children's way of living have grown progressively, although it‟s production is still scarce. Researches and scholars from childhood seek to understand the way of being a child through their daily life and specific contexts from cultures and society from which they belong, placing the child as a protagonist of it's own story and seeking the deconstruction from the term "infância" (childhood), which ends up in an image of a normative or outside the rule child. On the other hand the African child is placed as "out of place" for not following the pattern and rules of the European and north-american child: go to school from home (when they go to school), from there to another activity or responsibility: take care of siblings, help with the work at home, or with the income, among other activities. Through the presented picture in a previous experiment in a peripheral community near Mozambique, some initial questions were raised and subsequently formulated; bringing the issue about what is it like to be a child in a Mozambican society. The outlined objective was to know and understand the ways and dynamics of child socialization in this territory. It was understood that it was necessary a research in which the reality was present and the option was for the ethnography, the field research was made in a neighborhood in the Matola city, during a 5 months period. 5 children were chosen to participate in the research, which the acquaintanceship period was approximately 20 days, participating in their routines and domestic, community and school activities. By being inside their homes and their space of belonging , one can observe that the child in this environment belongs to the family and to the community, creating bonds and emotional development between people in different generation and their daily life, and responsibility that end up in their formation. Children have tasks and responsibilities that are assigned to them guided in the social division of work. Between activities one could observe that to play and the playful are always there, at home, at the street or at school. The playful and the laugh permeates the imagination and the childhood world, producing ways of existing, being and acting in the world that they share and belong. The school, the other place of belonging of a child and daily living, was a week attended place with lots of discussion, those situations and shared moments are brought in narratives, realizing that the writing way enable the reconstruction and description of the living moments and its reflections. It's understandable that there is a need of study in which one can deconstruct the ways that the childhood is imposed and enable ruptures in its universalization, understanding that there isn't only one childhood, from one specific context, based on the time-space in which they keep searching the right of a child of coming and going and of being protagonists in the world that they share and belong. This study also aims to contribute to the researches about childhood and African society.